2012
DOI: 10.1155/2012/741810
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Stem Cells: Future Perspectives

Abstract: The existence of stem cells in human amniotic fluid was reported for the first time almost ten years ago. Since this discovery, the knowledge about these cells has increased dramatically. Today, amniotic fluid stem (AFS) cells are widely accepted as a new powerful tool for basic research as well as for the establishment of new stem-cell-based therapy concepts. It is possible to generate monoclonal genomically stable AFS cell lines harboring high proliferative potential without raising ethical issues. Many diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…35 However, CD117+ AFS cell capacity of producing mature, functional neurons in vitro and in vivo is still under investigation. 41,90,91 Discussion and Conclusions AFS cell biological properties. The AF contains a broad range of cells, the majority of which are terminally differentiated and have limited proliferative capabilities.…”
Section: Cd117+ Amniotic Fluid Stem Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…35 However, CD117+ AFS cell capacity of producing mature, functional neurons in vitro and in vivo is still under investigation. 41,90,91 Discussion and Conclusions AFS cell biological properties. The AF contains a broad range of cells, the majority of which are terminally differentiated and have limited proliferative capabilities.…”
Section: Cd117+ Amniotic Fluid Stem Cellsmentioning
confidence: 95%
“…Since the first evidence that the AF could contain stem cells in 2003, 20 many groups have reported the isolation of multipotent and pluripotent cells. 33,34 In many studies, however, mixtures of unselected, non-clonal cells have been employed, 90 leading to conflicting results and uncertainty regarding the identity of the cell population employed. Indeed, stem cells within the AF harbor a spectrum of potency ranging from multipotent cells to unipotent committed progenitors (e.g., CD24+OB-cadherin+ renal progenitors, SOX2+ neural progenitors and CD133+ endothelial progenitors).…”
Section: Cd117+ Amniotic Fluid Stem Cellsmentioning
confidence: 99%
“…Additionally, we found that CD117-positive hAFS cells expressed the transcription factor OCT4, which works as a key factor in the transcriptional network to govern pluripotency and self-renewal of ESCs. The expression of stem cell markers indicated that the CD117-positive hAFS cells might share some characteristics with hESCs (Cananzi et al, 2012;Fhoov et al, 2009;Rosner et al, 2012Rosner et al, , 2011Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A aplicação de MSCs obtidas a partir do âmnio ou fluído amniótico na medicina regenerativa requer estudos extensivos quanto à sua aplicação clínica (Rosner et al 2012). Para a efetiva aplicação em terapias celulares em modelos in vivo, são necessários estudos quanto à caracterização dessas células por meio de marcadores funcionais e fenotípicos específicos, além de estudos experimentais pré-clí-nicos e clínicos, para entendimento de aspectos quanto ao seu mecanismo de ação (De Bakker et al 2013).…”
Section: Perspectivas De Terapias Celulares Em Animaisunclassified